БАС КИЙИМ КОНЦЕПТИНИҢ МИЛЛИЙ ДӘСТҮРЛЕРДЕ СӘЎЛЕЛЕНИЎИ - Пирниязова, А.Қ.; Аяпова, Қ. (FAN va JAMIYAT, 2022)
The article is devoted to the names of headdresses in the Karakalpak language. According to the tradition of the Karakalpak people, various headdresses were used. Women’s and men’s hats differ both in functions and in names. The linguistic nominations of the concept "headdress" are closely related to the tradition of the Karakalpak people. Headdresses are ritual elements.